Status and Influencing Factors of Social Media Addiction in Chinese Medical Care Professionals: A Cross-Sectional Survey - Luo, Aijing; Kong, Weitao; He, Haiyan; Li, Yuanyuan; Xie, Wenzhao (Frontiers in Psychology, 2022)
Background In modern society, social media addiction (SMA) has become a serious problem in many countries, including China. Almost every medical care professional has their own social media account. They are also at risk for SMA, but no SMA studies in Chinese medical care professionals have been published. This study aims to investigate the status and influencing factors of SMA among Chinese medical care professionals. Methods A cross-sectional study was conducted among 519 physicians and nurses from two randomly selected hospitals using a questionnaire that included the Social Networking Service Addiction Scale (SNSAS), Maslach’s Burnout Inventory-General Survey (MBI-GS), the General Self-efficacy Scale (GSES), and eight demographic datasets. Results This study’s findings showed that most of the participants’ (357,68.79%) scores reached 2.5 points (half of the highest possible score), indicating that SMA scores of Chinese medical care professionals were relatively high. Significant differences in SMA scores by age (p < 0.01), marital status (p < 0.01), professional title (p < 0.01), and working years (p < 0.01) were found. Income satisfaction (p < 0.01) and sleep quality (p < 0.05) were negatively correlated with SMA. The GSES score was not correlated with SMA (p = 0.377). Burnout significantly positively affected SMA (p < 0.01). Conclusion Our study found that the SMA scores of Chinese medical care professionals were relatively high. To reduce the SMA level of the medical care population, we should first start with reducing burnout, enabling medical care professionals to achieve sufficient sleep, increasing medical staff income, and providing more opportunities for promotion.